PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKATN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V SDN MELAYU MUHAMMADIYAH - Dian Lestari; Mutahharah (STKIP Subang, 2024)
This study aims to describe the improvement in the learning outcomes of fifth-grade students in Mathematics through the use of the TGT (Teams Games Tournaments) cooperative learning model at SDN Melayu Muhammadiyah. The type of research is Classroom Action Research (CAR) conducted in two cycles. The success indicators of the research are determined by cognitive learning outcomes, with a minimum passing grade (KKM) of ≥ 70 achieved by 90% of the 22 fifth-grade students. Data collection techniques used include observation and tests. The test results were analyzed using comparative descriptive techniques. The findings indicate that the implementation of the TGT learning model in Mathematics can enhance the cognitive learning outcomes of fifth-grade students at SDN Melayu Muhammadiyah. This is evidenced by the improvement in student mastery from the pre-cycle to Cycle I and Cycle II. In the pre-cycle, there were 3 students (13.04%) who achieved mastery with scores of KKM ≥ 70, which increased to 15 students (68.18%) in Cycle I, and in Cycle II, it further increased to 20 students (90.90%). Thus, it can be concluded that the TGT learning model can improve the Mathematics learning outcomes of fifth-grade students at SDN Melayu Muhammadiyah.